The Permian reptile Opisthodontosaurus carrolli: a model for acrodont tooth replacement and dental ontogeny. Issue 3 (6th December 2017) - Haridy, Yara; LeBlanc, Aaron R. H.; Reisz, Robert R.
Abstract: Continuous tooth replacement is common for tetrapods, but some groups of acrodont lepidosaurs have lost the ability to replace their dentition (monophyodonty). Acrodonty, where the tooth attaches to the apex of the jawbone, is an unusual form of tooth attachment that has been associated with the highly autapomorphic condition of monophyodonty. Beyond Lepidosauria, very little is known about the relationship between acrodonty and monophyodonty in other amniotes. We test for this association with a detailed study of the dentition of Opisthodontosaurus, an unusual Early Permian captorhinid eureptile with acrodont dentition. We provide clear evidence, both histological and morphological, that there were regular tooth replacement events in the lower jaw of Opisthodontosaurus, similar to its captorhinid relatives. Thus, our study of the oldest known amniote with an acrodont dentition shows that acrodonty does not inhibit tooth replacement, and that many of the characteristics assigned to lepidosaurian acrodonty are actually highly derived features of lepidosaurs that have resulted secondarily from a lack of tooth replacement. In the context of reptilian dental evolution, we propose the retention of the simple definition of acrodonty, which only pertains to the relative position of the tooth at the apex of the jaw, where the jaw possesses equal lingual and labial walls. This definition of implantation therefore focuses solely on the spatial relationship between the tooth and the jawbone, and separates this relationship from tooth development and replacement.